2016
DOI: 10.1016/j.physa.2016.03.104
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based modeling of lane discipline in heterogeneous traffic

Abstract: Designating lanes for different vehicle types is ideal road safety-wise. Practical considerations, however, require road sharing. Using a modified Nagel-Schrekenberg cellular automata model for two vehicle types (cars and motorcycles), we analyzed the interplay of lane discipline, lane changing, and vehicle density. In the absence of lane changing, the transition between free flow and congested states occurs at a higher vehicle (road occupation) density when the ratio of cars to motorcycles is increased. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In our previous model [21] wherein vehicles have a probability p λ to change lanes, it was observed that having low p λ impeded traffic flow, particularly for the case of cars wherein obstruction can occur. This effect is mitigated by ensuring that vehicles do not remain in between two lanes (p λ close to 1).…”
Section: Perceptions Of Lane Changingmentioning
confidence: 97%
See 2 more Smart Citations
“…In our previous model [21] wherein vehicles have a probability p λ to change lanes, it was observed that having low p λ impeded traffic flow, particularly for the case of cars wherein obstruction can occur. This effect is mitigated by ensuring that vehicles do not remain in between two lanes (p λ close to 1).…”
Section: Perceptions Of Lane Changingmentioning
confidence: 97%
“…Previously, we investigated the scenario wherein all vehicles may change lanes, with a probability p λ at which they are able to successfully change lanes [21]. Here, we focus on permitting only a fraction f of vehicles to change lanes with probability p λ = 1, with the remaining vehicles having p λ = 0.…”
Section: Fraction Of Lane Changing Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow of Hanjiang River can be obtained by model test or empirical formula. This paper belongs to the preliminary design stage, using empirical formula to calculate [8][9][10] .…”
Section: Environmental Load Calculationmentioning
confidence: 99%
“…As with the OV model, the NaSch model is also able to capture a wide range of traffic phenomenon such as the existence of a free-flowing and a congested phase. The simplicity of the rule-based evolution results in the NaSch model being highly popular in the traffic modelling community, from theoretically motivated studies [23,24] to studies with high practical applicability [25][26][27][28][29][30][31]. Most notably, the simplicity of the NaSch model -or discrete models in general -facilitates analytical predictions [32,33] on various macroscopic variables, which can provide valuable insights in understanding a complex system.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%